Karya Tari Warak Kruron - Nyoman Pasek Meisa Gunawan; Anak Agung Ayu Mayun Artati; Kompiang Gede Widnyana (Jurnal IGEL : Journal Of Dance, 2025)
Warak Kruron Dance is a new dance work inspired by the phenomenon of abortion and a cleansing process. The creator drew on these creative sources to produce a unified concept for the dance work. The creation of the Warak Kruron dance piece aims to educate the public about the importance of understanding the consequences of one's actions. Additionally, the creator incorporates several key aspects of choreography into the purification ritual as a symbolic vessel for a ceremony. The Warak Kruron dance piece was created using Alma M. Hawkins' creation method, which consists of three stages: exploration, improvisation, and formation. This dance piece is performed by nine male dancers and one female dancer, with a contemporary form consisting of three parts: part one, part two, and part three. The music for this dance piece uses MIDI (Musical Instrument Digital Interface) with a musical method (quadrasonic) equivalent to what is now called 4.0 surround sound, using four audio channels with speakers placed at the four corners of the listening space. This system allows for the reproduction of sound signals that are (entirely or partially) independent of one another. Quadraphonic surround sound with four channels can be used to recreate the highly realistic effects of a three-dimensional live concert experience at home. It can also enhance the listener's experience beyond the limitations of conventional two-channel stereo sound. Quadraphonic audio was the earliest consumer product in surround sound. Since its introduction to the public in the early 1970s, thousands of quadraphonic recordings have been produced. The makeup in the Warak Kruron dance piece uses minimalist makeup tailored to the concept of the production, and the costume design features a brown strait endek shirt, a kimono, harem pants, a sleeveless shirt, a kemben, and tile pants. Keyword: Warak Kruron, Aborsi, Prosesi, Contemporary